The Relationship of Family Centered Care Implementation with Mother's Stress and Satisfaction with Services in The Edelweiss Room (Perinatology) at Regional Hospital of Balung Jember District - Rahmawati, Ira; Mardiyah, Istna Abidah; Wahidah, Ami ‘Alaili (Pediomaternal Nursing Journal, 2022)
Introduction: Neonatal intensive care causes high maternal stress, and low interaction between mother and baby are suspected to be a stressor. The role of the mother needed to participate in neonatal care. However, mothers want to monitor the condition of neonates during treatment. This purpose of study to analyze the correlation between family center care, stress and maternal satisfaction in the Edelweiss (Perinatology) at RSD Balung Jember. Methods: A cross-sectional study was conducted among 124 post partum mothers whose babies were treated in the perinatology room with consecutive random sampling. Family center care, stress, and maternal satisfaction questionnaires were used. A Chi-square test was used to analyze to answer the research Results: The results among respondents had high levels of family centered care implementation (63.7%), low maternal stress (51.6%), and high levels of maternal satisfaction (58.1%). There is a correlation between between family centered care implementation with maternal stress (X2 = 8.14; p-value = 0.004), and stress with maternal satisfaction (X2 = 19.3; p-value = 0.00). Mothers with high levels of family centered care implementation will prevent 0.2 times experiencing stress (OR = 0.16; 95% CI = 0.07-0.38), and if maternal satisfaction is high then 3 times will tend to have low stress (OR = 2.89; 95% CI = 1.38-6.06). However, there isn't correlation between family centered care implementation and satisfaction mother (X2 = 0.83; p-value = 0.36). Perhaps, maternal characteristics to be a factor. Conculusion: Family center care services can meet the needs of parents and improve the quality of nursing care in the perinatology room for babies, parents and families so as to increase satisfaction with the services provided.